2022
DOI: 10.3352/jeehp.2022.19.29
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced numeracy skills following team-based learning in United States pharmacy students: a longitudinal cohort study

Abstract: Purpose: The literature suggests that the ability to numerate cannot be fully understood without accounting for the social context in which mathematical activity is represented. Team-based learning (TBL) is an andragogical approach with theoretical links to sociocultural and community-of-practice learning. This study aimed to quantitatively explore the impact of TBL instruction on numeracy development in 2 cohorts of pharmacy students and identify the impact of TBL instruction on numeracy development from a so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The review results indicated that Numeracy skills greatly enhanced the HSRT-N domain in pharmacy students (Carpenter et al, 2022;Genlott & Grönlund, 2013). Reading skills were enhanced in writing skills.…”
Section: Motivational Outcomes Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The review results indicated that Numeracy skills greatly enhanced the HSRT-N domain in pharmacy students (Carpenter et al, 2022;Genlott & Grönlund, 2013). Reading skills were enhanced in writing skills.…”
Section: Motivational Outcomes Researchmentioning
confidence: 99%
“…Some important points which are the strengths of this SLR are the disparity in achievement in literacy skills shows that not all students can solve broadly related general problems in everyday life (Anwar, 2021;Carpenter et al, 2022;Johar et al, 2022). As a result, literacy and numercy research to support 21st century skills is urgently needed, especially in remote and isolated areas.…”
Section: Recommendations For Future Researchmentioning
confidence: 99%